Ecological effects of the herbicide linuron in tropical freshwater microcosms - Daam, MA
Effects of a single application of the photosynthesis-inhibiting herbicide linuron (0, 15, 50, 150, and 500 mu g/L) on the ecology of outdoor plankton-dominated microcosms were studied in Thailand. As a result of the decreased photosynthesis, DO and pH decreased while EC, alkalinity and nutrient concentrations increased. Chlorophytes belonging to the genera Scenedesmus, Coelastrum and Pediastrum were the most sensitive taxa, whereas several other chlorophytes, diatoms, and cryptophytes increased in abundance. Tolerant taxa appeared to be less digestable for several zooplankton taxa, which subsequently decreased in abundances. Chamaesiphon sp. (Cyanobacteria) was the most susceptible periphyton species. As a consequence of functional redundancy, effects of the herbicide on the chlorophyll-a content of periphyton and especially phytoplankton did not always reflect the effects noted on community level. (C) 2008 Elsevier Inc. All rights reserved.